1996
DOI: 10.1097/00006534-199601000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Silicone Gel Breast Implant Rupture by Ultrasonography

Abstract: To prospectively evaluate the efficacy of ultrasonography in the diagnosis of ruptured silicone gel breast implants, 98 patients (192 implants) underwent preoperative breast ultrasonography prior to silicone gel breast implant removal. The prevalence of implant rupture confirmed at surgery in this group of patients was 62 of the 192 implants (32 percent). Of the 60 implants diagnosed as ruptured by ultrasonography, 46 were confirmed as having visible defects at surgery (true positive) for a positive predictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 20 publications
1
15
2
1
Order By: Relevance
“…16,22,23 The falsenegative and false-positive rates found in the present work were 25% and 12%, respectively, with 30% sensitivity, 81.13% specificity and a likelihood ratio of 1.59. These rates are related to the high prevalence of non-specific echographic signs in both ruptured and nonruptured implants.…”
Section: Resultssupporting
confidence: 44%
See 2 more Smart Citations
“…16,22,23 The falsenegative and false-positive rates found in the present work were 25% and 12%, respectively, with 30% sensitivity, 81.13% specificity and a likelihood ratio of 1.59. These rates are related to the high prevalence of non-specific echographic signs in both ruptured and nonruptured implants.…”
Section: Resultssupporting
confidence: 44%
“…It was observed that, in studies that included samples that were asymptomatic for rupture, the sensitivity was lower than what was described in the present study. 16,19,22,23 In our study, ultrasound showed limitations, thereby indicating that in patients with major folds it is extremely difficult to rule out rupture and that this should be investigated through magnetic resonance imaging. Ultrasonography can be used as the first test in the assessment of breast implants in asymptomatic patients, followed by mammography.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…In augmented breasts the sensitivity ranged from 75% to 80% and from 70% to 75% for MRI and ultrasound, respectively; the specificity for implant rupture is 95% and 90%, respectively [21][22][23]. Furthermore, MRI is useful for evaluating capsular contracture.…”
Section: Discussionmentioning
confidence: 99%
“…Ein Nachteil der Mammasonographie liegt in der eingeschränkten Beurteilbarkeit des Ausmasses einer Kap-selruptur und in der Abhängigkeit vom jeweiligen Untersucher [7,8] . In Studien wird im Nachweis von Implantatrupturen daher über eine variable Sensitivität von 59-89% und eine Spezifität von 69-98% berichtet [7,10,11] .…”
Section: Introductionunclassified